Design of a Low Power and High-Efficiency Charge Pump Circuit for RFID Transponder EEPROM [Zasnova vezja crpalke naboja z majhno mocjo in visoko ucinkovitostjo za RFID transponder EEPROM] - Rahman L.F.; Alam L.; Marufuzzaman M. (Society for Microelectronics, Electric Components and Materials, 2023)
The charge pump (CP) circuit is an essential part of a radio frequency identification electrically-erasable-programmableread-only memory (RFID-EEPROM). A CP circuit generates a boosted output voltage that is greater than the power supply voltage. However, the performance of the diode configured CP circuits is strongly affected by the extra power dissipation and the parasitic capacitance. The parasitic capacitors of the CP circuit are also responsible for increased power consumption. In this research, an improved CP circuit is designed for achieving higher output voltage gain by reducing the parasitic capacitances. Moreover, the proposed course consumes less power, which makes it more suitable for low power applications like RFID transponder. The proposed CP circuit is using the internal boosted voltage for backward control where active controls are applied to the charge transfer switch (CTS) to eradicate the reverse charge sharing trends. Simulated results showed that by using 1 pF pumping capacitor to drive the capacitive output load, the proposed circuit generates 9.56 V under 1.2 V power supply. In comparison with other research, works, this CP circuit consumes less power (only 15.26 ?W), which is lower than previous research works. Moreover, the proposed CTS CP circuit can operate with the efficiency of 79.3%, which is found higher compared to other research works. Thus, the proposed design will be an essential module for low power applications like RFID transponder EEPROM. Copyright 2020 by the Authors.